Higher Education Service Quality Based on Students’ Satisfaction in Pakistan - Abdul Ghaffar Mastoi; Lu Xin Hai; Wimonsiri Saengkrod (European Scientific Journal, ESJ, 2019)
Universities in the modern world are expected to seek and cultivate new knowledge, provide the right kind of leadership and strive to promote equality and social justice. The quality of education is an important factor considered for attracting and retaining students as it is a substantial investment made by their parents. Hence, delivering quality service has become an important goal for most higher education institutions (HEIs) and for distinguishing the institutions among other competitors. The general objective of the study is to investigate the satisfaction level of students enrolled in undergraduate and/or graduate programs from different universities in Pakistan and understand: the level of service quality with respect to administrative services, core educational quality, support facilities, physical environmental quality and transformative quality, and overall level of students’ satisfaction all university services. A cross-sectional study design was conducted on students of the university’s selected using a stratified random sampling technique. Data was collected from 500 questionnaires and analyzed through SPSS. By using multiple linear regression analysis, it revealed which factor was playing how much role in the prediction of students’ satisfaction. It was also found that apart from administrative quality of the university all of abovementioned services contributed significantly towards satisfaction level of university students. As student’s satisfaction has been positively associated with their performance in university as well as later in their workplaces, it would appear to be detrimental that this aspect of university student’s dependence on the service quality provided by higher education institutions should be ignored. It eventually affects the productivity of the workforce of a society and eventually economy of a nation.